Articulating Qur’anic Values in Javanese Cosmology: A Hermeneutical Reading of Kawruh Jiwa of Ki Ageng Suryomentaram - Safei, Abdullah; Muhammad Irawan Taqwa; Agus Handoko; Zakaria Abdiwali Muhammed (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2026)
This study argues that Ki Ageng Suryomentaram’s (KAS) Kawruh Jiwa is not merely an indigenous psychological framework but a sophisticated vernacularization of Qur’anic values within Javanese intellectualism. While previous scholarship focuses on its psychological dimensions, this research positions Kawruh Jiwa as a dialectical product between divine revelation and local cosmology. Employing a qualitative method rooted in Gadamerian philosophical hermeneutics—specifically the concept of